Evaluating the Effectiveness of the Qanaah-Based Coping Intervention to Improve Psychological Well-Being in Islamic Boarding School Students: A Quasi-Experimental Study - Khusumadewi, Ari; Pramesti, Mayang; Lianawati, Ayong (Universitas Negeri Padang, 2025)
This study aimed to assess the success of qanaah coping as a training approach to improve the psychological well-being of students. Qanaah in Islam is a disposition of accepting and finding contentment in the results of one's endeavours, while eschewing sentiments of discontent and inadequacy. The participants in this study were eight students demonstrating diminished psychological well-being attributable to maladaptive thought habits. The study utilised a one-group pretest-posttest design, implementing cognitive restructuring via qanaah coping inside a group counselling framework. The study employed a psychological well-being scale with 26 reliable items to assess the intervention's efficacy. The instrument had substantial dependability, evidenced by a Cronbach’s alpha coefficient of 0.898. Given that the significance value exceeded 0.05, the instrument was considered acceptable. The results indicated a t-score of -5.767 and a significance level of 0.001, which is below 0.05, signifying statistical significance. The mean psychological well-being score improved from 60.685 in the pre-test to 109.105 in the post-test, resulting in the null hypothesis being rejected. The qanaah coping technique was determined to be beneficial in enhancing the psychological well-being of students in Islamic boarding schools.